Handling and Recovery of Religious Conflict Victims by Local Governments in Indonesia; A Study of Sunni-Shi'a Conflict in Sampang and Pasuruan - Soleh, Moh.; Habibullah, Abdul Wachid; Shalihin, Habibus; Wicaksana, Dio Ashar; Fikri, Muhammad Ali (TRUNOJOYO LAW REVIEW, 2024)
One of the religious conflicts in Indonesia is the Sunni-Shia conflict in Sampang Regency and Pasuruan Regency. This conflict has attracted the global community's attention because the handling process deviated from the values of equality in religion and ignored human rights principles. This study was conducted to determine the role of local governments in handling and recovering victims of religious conflicts. This study is expected to contribute to efforts to handle and recover victims of religious conflicts in Indonesia, especially by local governments. The empirical legal research method uses primary and secondary data sources. Practices of Handling and Recovering Victims of Social Conflicts Based on Religion and Belief in Pasuruan Regency and Sampang Regency, namely: 1) There is no policy at the regional level in handling social conflicts, 2) There is no particular regional budget for handling social conflicts; 3) Community participation (non-state actors) in handling social conflicts in Pasuruan Regency has not been maximised; 4) Post-conflict recovery only focuses on physical recovery.